PENGARUH PEKERJAAN-KELUARGA DAN DUKUNGAN SOSIAL SERTA KECERDASAN EMOSIONAL TERHADAP STRES KERJA DAN KINERJA PERAWAT WANITA DI RSD dr. SOEBANDI JEMBER - Yulia, Avira Risqiana (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2017)
Abstract: The purpose of this study among others, to analyze the effect of the work-family conflict, social support and emotional intelegence on work stress and job performance among female nurses in RSD dr. Soebandi Jember. This study was a research explanation. The study population was 237 female nurses of RSD dr. Soebandi Jember. Sample was 120 people. Methods of data analysis used SEM. The result show that work-family conflict significantly influence work stress. Work-family conflict significantly influence job performance. Social support significantly influence work stress. Social support significantly influence job performance. Emotional intelegence significantly influence work stress. Emotional intelegence significantly influence job performance. Work stress significantly influence job performance.Keywords: Work-family conflict, Social support, Emotional intelegence, Work stress, and Job performance